Proclamando a los reyes en la periferia Entre contextos locales y proyectos imperiales (Santiago de Chile, siglo XVIII) - Valenzuela Marquez, Jaime (2008)
This article studies the royal proclamations, taking into account the political characteristics of the spanish monarchy during the XVIII century. The analysis in centered on the reproduction of a ceremony that was carried out, with local differences, all arround the empire. We will analyse the proclamations of Charles III and Charles IV, since in these ceremonies the central problems wich worried the chilean authorities on those days, were deployed. Among these we will pay special attention to the strategies deployed to incorporate mapuche leaders into the main celebration that legitimate the royal power.